The family Euphorbiaceae, source of vegetable oils for the technochemical industry - M. J. Pascual Villalobos; E. Correal Castellanos (Grasas y Aceites, 1992)
The family Euphorbiaceae includes a huge number of species some of which provide important raw materials such as rubber, cassava, waxes and oils. In this study, the general botanical and chemical characteristics of this family are described firstly together with the chemical composition of their seed oils and a comparison with those of other families. Secondly, other chemical constituents of economic interest are reviewed and compared with the species already used for food, industry and medicine purposes. A further revision is included on some of its genus with potential interest and on current industrial oil crops such as Ridnus, Euphorbia, Aleurites, Sapium, Jatropha, etc. Finally, from an economic point of view, future prospects of some of these oils as raw materials for the chemical industry are given.